Strategic business model typologies evident in the Chinese real-estate industry - Liu, Guiwen; Li, Kaijian; Shrestha, Asheem; Martek, Igor; Zhou, Yang (International Journal of Strategic Property Management, 2018)
The Chinese real estate industry has emerged over recent decades as one of the key drivers of Chinese economic growth and attracted thousands of players nationwide. Yet, despite the continuing importance of the real-estate industry in China, there has not been any work done to identify nor describe the strategic business models used by enterprises within the sector. This study fills this gap in the literature. This paper begins by building a framework for studying the strategic business models used within the Chinese real-estate industry, and then goes on to identify the generic models that exist in the industry. A two-step cluster analysis of 117 Chinese real-estate companies was carried out over seven parameters identified in the literature as impacting business models: 1) clients, 2) products offered, 3) market locale, 4) financial structure, 5) value chain embeddedness, 6) core competency, and, 7) revenue source. Five generic strategic business models that characterize the Chinese real-estate industry were identified: 1) commercial property model, 2) government servicing model, 3) cost efficiency model, 4) asset management model, and, 5) high-turnover model. The findings will assist industry practitioners in evaluating and informing their own competitive positions within the Chinese real-estate industry.